Modified correlation equation in the FSDP-related void-based model for As₂S(Se)₃ chalcogenide glasses - Kavetskyy, T.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Revised in this work is the correlation equation Q₁ = 2.3×π/D in the FSDPrelated
void-based model for As₂S(Se)₃ chalcogenide glasses between the first sharp
diffraction peak (FSDP) position, Q₁, and nanovoid diameter, D, are modified to be
presented in the form of Q₁ = 1.75×π/D, taking into account a newly deduced formula for
positron lifetime, τ₂, versus void radius, R. It is valid for those molecular substrates for R
up to 5 Å and when no orthopositronium (o-Ps) or very small fractions of o-Ps
components are observed in positron annihilation lifetime spectroscopy.